The beyond mum - Burke, Kevin (Henry Stewart Talks, 2009)
Motherhood, What women want turned into a career, A guy's perspective, Pregnancy suit experience, Mom project and Light Iris, Draw today's mom, Duality of motherhood, Psycho: why we're scared, Paying attention to behavior and attitude, Consumer's power, Mom's market, Financial management in the household, What's a marketer to do?, Mom's circle of influence, Moms online, US adult internet users and penetration, Mom bloggers, Factors in evaluating online ads, Online marketing communication preferences, Personal email usage, Books on marketing to moms, Platforms to use